Pengaruh Perbandingan Komposisi ZnO dan TiO2 dalam Dye-Sensitized Solar Cell (DSSC) pada Dye Kangkung (Ipomoea aquatica) - Agus Supriyanto; Deny Kurniawan; C Cari (Universitas Sebelas Maret, 2020)
Abstract: Zinc oxide has the chemical formula ZnO, while titanium oxide has the chemical formula TiO2. Zinc oxide and titanium dioxide are inorganic compounds. Zno and TiO2 are often used for Dye-Sensitized Solar Cell (DSSC). This research was conducted by mixing ZnO and TiO2 as a photoanode. A mixture of ZnO and TiO2 is prepared by mixing ZnO and TiO2 in a ratio of 1:1, 1:2, 1:3 and then dissolved in ethanol. The natural dye used is water spinach (Ipomoea aquatica) extract. The absorbance of natural kale dye has two quite high absorption spectra, ranging from 435-480 nm and 610-800. Each absorption spectrum has two photon absorption peaks at the wavelengths of 476 nm and 611 nm. The absorption values were 3.35724 a, u and 3.15647. Fabrication is carried out using FTO glass with a working area of 1 cm x 1 cm. The efficiency results obtained were ZnO/TiO2 (1:1) nanocomposites with an efficiency (η) of 0.08165%, ZnO/TiO2 (1:2) nanocomposites with an efficiency (η) of 0.20743% ZnO/TiO2 nanocomposites (1:3) with an efficiency (η) of 0.24044%.Abstrak: Seng oksida memiliki rumus kimia ZnO, sedangkan titanium oksida yang memiliki rumus kimia TiO2. Seng oksida dan titanium dioksida adalah senyawa anorganik. Zno dan TiO2 sering digunakan untuk Dye-Sensitized Solar Cell (DSSC). Penelitian ini dilakukan dengan mencampurkan ZnO dan TiO2 sebagai fotoanoda. Campuran ZnO dan TiO2 dibuat dengan mencampurkan ZnO dan TiO2 dengan perbandingan 1:1, 1:2, 1:3 kemudian dilarutkan dalam etanol. Pewarna alami yang digunakan adalah ekstrak kangkung (Ipomoea aquatica). Absorbansi dari dye alami kangkung memiliki dua spektrum penyerapan yang cukup tinggi yaitu berkisar antara 435-480 nm dan 610-800. Masing-masing spektrum penyerapan memiliki dua puncak penyerapan foton yaitu pada panjang gelombang 476 nm dan 611 nm. Nilai absorbasnsi berturut-turut yaitu 3.35724 a,u dan 3.15647. Fabrikasi dilakukan menggunakan kaca FTO dengan luas kerja 1 cm x 1 cm. Hasil efisiensi diperoleh nanokomposit ZnO/TiO2 (1:1) dengan efisiensi (η) sebesar 0,08165%, nanokomposit ZnO/TiO2 (1:2) dengan efisiensi (η) 0,20743% nanokomposit ZnO/TiO2 (1:3) dengan efisiensi (η) 0,24044%.